Regeneration Methods Dipterocarpus Specifs in India - Thangam, E. S. (Indian Forester, 1982)
The complex nature of the tropical rain forests containing more than a few hundred species with only 30 to 40 commercially important trce species has been indicated. The ten Dipteroearpus species found in India can De divided into those occurring in the Eastern group consisting of the foothills of eastern end of the Himalayas and the Patkoi hill ranges bordering Burma i.e. Assam, Arunachal Pradesh, Megholaya, Manipur, Mizoram, Nagaland and Tripuro and the Andaman Island and those occurring in the Western group consisting of the Western ghat ranges along the west coast i.e. Tamil Nadu, Kerala and Karnataka, While the Eastern group contains Dipteroearpus status, D. costauss D. grandiflorus, D. kerrii, D. macrocarpus, D. gracilis. D. tuberculates and D. turbinatus, the Western group contains D. indious and D. bourdillonil only. The locality factors like temperature, rainfall, humidity wind and soil which affect the growth of the species are described. The regeneration practice adopted condsts of natural regeneration mathods and artificial regeneration methods. The natural regeneration methods adopted through successful in the Eastern group, are only of varying degrees of success in the Westeern group. The artificial regeneration method is adopted successfully in Eastern group in Tripura , while the effort in western group have not been successful. The experience gained shows that the natural regeneration methods adopted to regenerate the Dipterocarpus spp. Were successful due to the high percentage of its incidence, which helped to provide adequate advdnce growth in the forests.